Prevalence and factors associated with diabetes-related distress among patients with type 2 diabetes mellitus in a South Indian secondary care hospital - R., Navaneethakrishnan; Kuriakose, Cijoy K. (International Journal of Research in Medical Sciences, 2025)
Background: Diabetes related distress (DRD), though well known, is under-recognized in the Indian subcontinent. Existing literature is mostly from tertiary or teaching hospitals located in urban areas. The prevalence and determinants of DRD among non-urban settings is not well known. This study aims to fill this knowledge gap by investigating the same among patients with type 2 diabetes mellitus (T2DM) in a South Indian secondary care hospital. Methods: 227 consecutive patients with T2DM were administered pre-validated diabetes distress scale questionnaire and their responses documented. The prevalence of distress in each of the four domains and as a whole was measured and the association with various factors were identified using appropriate statistical methods. Results: 165 (72.7%), 164 (72.2%), 176 (77.5%) and 155 (68.3%) of patients experienced emotional distress, physician-related distress, regimen-related distress and interpersonal distress respectively. Overall, 165 (72.7%) had clinically significant diabetes-related distress in the study. Occurrence of hypoglycemic episodes (p 0.02), having high body mass index (BMI) (p 0.03) and non-adherence to a diet plan (p 0.03) were associated with increased distress in various domains. Conclusions: Three out of four (165/227; 72.7%) adult patients living with T2DM reported experiencing DRD, a significantly higher prevalence than shown in previous studies. This highlights the need to incorporate DRD screening and management as part of routine care of T2DM. Prevalence of DRD was higher among patients who experienced hypoglycemia episodes in the month prior to the assessment. Scrupulous avoidance of hypoglycemia may help to reduce DRD among patients living with T2DM.